THE DETERMINANCE OF THE FINANCIAL BEHAVIOR AMONG GRADUATE STUDENTS IN INDONESIA - ., Nyoto; Renaldo, Nicholas; Karuppannan, Gunasegaran; Bhuiyan, Abul Bashar; Kumarasamy, Mokana Muthu (Australian Finance & Banking Review, 2021)
The lifestyle of adolescents who migrate to work and college will largely determine their future. Concerns about economic conditions can cause problems with their behavior. This research has aimed to explore the most influential factors on Financial Behavior among graduate students in Indonesia. The Primary data collected by distributing questionnaires using a Likert scale. There are 239 samples have collected based on the combination of purposive and convenience sampling methods. The study used descriptive statistical techniques and path analysis techniques for data analysis. Based on path analysis results, study findings indicate that there is a significant influence of financial knowledge on financial self-efficacy; financial self-efficacy and financial knowledge on financial behavior; financial attitude and financial self-efficacy on financial behavior but there is no significant influence of financial knowledge on financial behavior. The study results also showed that adolescent habits are still not good but can be improved through education such as character education and achievement of a better motivation to deal with economic problems. The study recommended that the good habits can be passed on to friends of his age, especially adolescents so they can have a good future. JEL Classification Codes: F36, G02, A23.